OsHYPK/NatA-mediated N-terminal acetylation regulates the homeostasis of NLR immune protein to fine-tune rice immune responses and growth - Huang, Yaqian; Gong, Xiaodi; Shi, Hui; Wang, Peiyi; Yuan, Yundong; Kong, Cuilian; Zhou, Jie; Wu, Dianxing; Liang, Yan; Wang, Yonghong; Wang, Jing (Cell reports, 2025)
Keeping nucleotide-binding leucine-rich repeat (NLR) protein at appropriate levels is critical for plant survival. Huntingtin Yeast Partner K (OsHYPK) was previously identified as a positive regulator of N-terminal acetyltransferase A (NatA) activity in rice. Here, we find that oshypk shows enhanced resistance to Magnaporthe oryzae (M. oryzae). Through screening for suppressors of oshypk (soh), we identify suppressor soh74, which contains a mutation in RESISTANCE TO P. SYRINGAE PV MACULICOLA1 (RPM1)-like NLR protein (RPM1-L1) and exhibits compromised resistance to M. oryzae. Mechanistically, declined N-terminal acetylation (NTA) degree in oshypk leads to protein accumulation of RPM1-L1, contributing to enhanced disease resistance. To restrict RPM1-L1 accumulation, OsHYPK is expressed at high levels under normal conditions. However, pathogen infection reduces OsHYPK level to release the inhibition on RPM1-L1, leading to immune activation. This study reveals a vital pathway in which OsHYPK/NatA-mediated NTA rapidly fine-tunes NLR-mediated immune response.